Synthesis and Physical Characterization of 4-(anthracen-10-yl)-1-(4-mthoxyphenyl)-3-phenoxyazetidin-2-one as a New Cis 2-azetidinone - Abraham F. Jalbout; Mohammad Nazari; Aliasghar Jarrahpour (Molbank, 2007)
The synthesis of 4-(anthracen-10-yl)-1-(4-methoxyphenyl)-3-phenoxy azetidin-2-one is presented here. The AM1 calculations for characterizing the physical properties of the molecule are also given.